Adoption of self-regulated learning strategies for improving academic performance of adult learners in literacy programmes in Anambra state - Madu, C. O.; Okechukwu, U. D. (Journal of Research in Adult and Continuing Education, 2023)
This study aimed at determining the extent of adoption of self-regulated learning strategies for improving academic performance in literacy programmes in Anambra State with particular focus on self-monitoring and self- evaluation strategies. Two research questions and two null hypotheses guided the study. Descriptive survey research design was used for the study. A total of 44,403 which comprised 18,330 male and 26,073 female adult learners in 286 literacy centres in 2020/2021 academic session in Anambra State were used as the population of the study. A sample size of 888 (366 males and 522 females) was drawn from the population using proportionate stratified random sampling technique. The instrument for data collection was a structured questionnaire developed by the researchers. Cronbach Alpha was used to determine the reliability of the study. The internal consistency of the instrument yielded an overall reliability coefficient value of 0.88. The instrument was validated by three experts. Mean statistics and standard deviation were used to answer research questions while t-test statistics was used to test the null hypotheses at 0.05 level of significance. The findings revealed that adult learners adopt self-monitoring and self-evaluation strategies to a high extent. The findings on the hypotheses showed that there was no significant difference on the adoption of self-monitoring and self-evaluation strategies. The researchers recommend that adult educators or facilitators should emphasis the teaching of self-regulated learning strategies to enable adult learners acquire self-regulated learning skills. This will enable them adopt other self- regulated learning strategies like goal setting and planning for better performance in literacy programmes, among others.